The selectivity in lung cancer surgery - Sanjines-Bros, Aníbal (Cirugía del Uruguay, 1975)
This is a report from the Thorax Diseases Institute, abcut surgery of lung cancer. For the evaluation of the cases TNM international classification was adopted, considering three degrees of extension: localized cancer or with lobar extension; cancer with regional extension and invading cancer. In stage I late results were excellent and the "cure-aiming" resection could be performed in all cases. Results were totally opposite in stage III. In the controversial stage 11, the results obtaine.d are dubious. Invasion of mediastinal lymph nades makes the prognosis obscure. The kind of metastasis, the histologic type, and the location of the invaded lymph nodes are fundamental elements in thc therapeutic decision. The previous exploration of the mediastinum in sorne circumstances may be precisely indicated. Prognosis fundamentally depends on the extension of the cancer and the general condition of the patient. Age, and cardiorespiratory condition are of utmost importance. The need of a correct selection of patients is remarked. Surgery without a selective criterion may have an adverse effect. In .this sense, the authors lay stress on the results obtained in the group of exploratory thoracotomy, in which half of the pa1:ients died in the first three months following surgery.